Vehicle routing problem with pick-up and delivery using genetic algorithm / Muhammad Shahfiq Zazali and Wan Muhamad Nasrin Aiman Mat Soti - Zazali, Muhammad Shahfiq; Mat Soti, Wan Muhamad Nasrin Aiman (2022)
The Vehicle Routing Problem with Pickup and Delivery is a logistics problem where both pickup and delivery of goods is done simultaneously. The constraint for the problem is that it must start and end at the depot while capacity when reaching nodes must not exceed the capacity of the vehicle. The objective of solving this problem is to find the optimal solution which then will reduce the cost for the route taken by the vehicle. Since the traditional approach of solving this problem, which is the exact solution, will consume a lot of time, Genetic Algorithm is proposed. Another focus we will be looking at is the effect of changing the operator used, where we will create two GA models where each model consists of only one operator to differentiate which model provides a better solution. Our findings show that GA with a mutation operator is better at solving the problem compared to crossover operator because it provides a smaller total distance within a given iteration while GA with a crossover operator does not have any change at all until the iteration stops. The most optimal solution for the data used is 233641.009 calculated using a software that uses the Ruin and Recreate principle. By the end of the study, both objectives are satisfied.